1957
DOI: 10.1128/jb.73.4.516-521.1957
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON THERMOPHILIC SULFATE REDUCING BACTERIA I. Sporovibrio desulfuricans as Clostridium nigrificans

Abstract: Elion (1924) was the first to isolate a thermophilic sulfate reducing bacterium in pure culture. He named the organism Vibrio thermodesulfuricans, and reported that it was capable of sulfate reduction betveen 30 and 65 C, wvith an optimum of 55 C. Baars (1930) and Kluyver and Baars (1932) reisolated V. thermodesulfuricans, and carried out a comparative study of this organism and Vibrio desulfuricans. They reported that it was possible to adapt cultures of V. desulfuricans, initially capable of growth only at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

1959
1959
2006
2006

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 6 publications
3
23
0
Order By: Relevance
“…Serology. The immunization procedures for obtaining rabbit sera against sulfate-reducing bacteria were those described previously (7). Ouchterlony immunodiffusion studies were carried out as described by Postgate and Campbell (15), except that the plates were incubated at 16 C. Cross-absorptions were performed by using 8 to 10 mg (dry weight equivalent) of frozen-and-thawed bacteria per ml of serum and removing the sediment by centrifugation after 20 to 30 min at ambient room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Serology. The immunization procedures for obtaining rabbit sera against sulfate-reducing bacteria were those described previously (7). Ouchterlony immunodiffusion studies were carried out as described by Postgate and Campbell (15), except that the plates were incubated at 16 C. Cross-absorptions were performed by using 8 to 10 mg (dry weight equivalent) of frozen-and-thawed bacteria per ml of serum and removing the sediment by centrifugation after 20 to 30 min at ambient room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Clostridium nigriJicans (NCIB 8395) was received from Dr. J. Senez as one of Dr. R. L. Starkey's best sporulating strains of D. thermodesulphuricans. This strain was identified by Campbell, Frank & Hall (1957) as Clostridum nigri$cans. The stock culture was subcultured a t intervals of not more than a week in a lactatemineral salts medium (medium A of Butlin, Adams & Thomas, 1949) supplemented with 0.1% of Difco yeast extract.…”
Section: Methodsmentioning
confidence: 99%
“…It was concluded that the ability to bring about depolarization a t the cathode was the most important factor in the stimulation of corrosion by sulphate reducers and that this depended on the possession of a suitable hydrogenaae system by the organism concerned. Confirmatory evidence came from the study of the effect on polarization curves of two strains of the sporeforming thermophilic sulphate reducer, shown by Campbell, Frank t Hall (1957) to be identical with the food spoilage organism, Clostridium nigrificans. A hydrogenase positive strain (NCIB 8351) effected cathodic depolarization ; a hydrogenase negative strain (NCIB 8353) did not .…”
Section: Anaerobic Corrosionmentioning
confidence: 95%